2023
DOI: 10.3390/jcm12082822
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Two Types of Exercise Interventions on Leptin and Omentin Concentrations and Indicators of Lipid and Carbohydrate Metabolism in Males with Metabolic Syndrome

Abstract: Leptin (LEP) and omentin (OMEN) are proteins whose concentrations change with the development of the metabolic syndrome (MetS). There are few intervention studies using various forms of physical activity in people with MetS that aim to determine the impact of physical exercise on the fluctuations of the presented hormones, and their results are contradictory. The present study aimed to examine the effect of two types of exercise intervention on LEP and OMEN concentrations and indicators of lipid and carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…The development of muscle mass through aerobic-resistance training maintained body weight at a similar level, despite a reduction in fat tissue. On the other hand, in the group with aerobic intervention, a significant decrease in BMI between measurements reflects a decrease in body weight due to lost fat tissue, as demonstrated in previous paper 35 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The development of muscle mass through aerobic-resistance training maintained body weight at a similar level, despite a reduction in fat tissue. On the other hand, in the group with aerobic intervention, a significant decrease in BMI between measurements reflects a decrease in body weight due to lost fat tissue, as demonstrated in previous paper 35 .…”
Section: Discussionsupporting
confidence: 61%
“…The study was registered in the Australian New Zealand Clinical Trials Registry under the registration number ACTRN12622001394730 (31/10/2022) and followed CONSORT guidelines. A detailed description of the research methods was presented in previous papers 31 , 34 , 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that the ADIPO/LEP ratio decreased significantly after 6 weeks of aerobic intervention. The occurring relation resulted from a significant increase of LEP level, presented in our previous work [42] and the lack of significant changes in the level of ADIPO during the analyzed period. LEP can react to the changes taking place in the population of people with MetS faster than ADIPO.…”
Section: Discussionmentioning
confidence: 57%
“…The study was designed as a randomized, prospective controlled study. A detailed description of the research methods was presented in previous papers [41,42]. The aim of this study was to compare the 12-week effect of two types of physical training on ADIPO and IL-8 levels and carbohydrate metabolism indices in men with metabolic syndrome (MetS), compared to men with MetS not undertaking physical activity (control group CG).…”
Section: Methodsmentioning
confidence: 99%